Accelerated catalytic activity of Pd NPs supported on amine-rich silica hollow nanospheres for quinoline hydrogenation. Issue 11 (4th May 2017) - Guo, Miao; Li, Can; Yang, Qihua
Abstract : The ultra-small Pd NPs stabilized by the amine-rich silica hollow nanosphere with a TOF as high as 5052 h −1 are among the most active solid catalysts for quinoline hydrogenation. The high catalytic activity could be mainly attributed to the ultra-small particle size and high surface electron density of Pd NPs. Abstract : Tuning the catalytic performance of metal nanoparticles (NPs) is very important in nanocatalysis. Herein, we report that amine-rich mesoporous silica hollow nanospheres (HS-NH2 ) synthesized by one-pot condensation could efficiently stabilize ultra-small Pd NPs and also increase the surface electron density of Pd NPs due to the coordinating and electron-donating effects of the amine group. Pd NPs supported on HS-NH2 afford TOF as high as 5052 h −1 in quinoline hydrogenation reaction and are much more active than Pd/C with a TOF of 960 h −1 as well as most reported solid catalysts. The intrinsic activity of Pd NPs increases as the particle size of Pd decreases, revealing that quinoline hydrogenation is a structure-sensitive reaction. The results of TEM, XPS, CO adsorption and CO stripping voltammetry indicate that the high activity of Pd NPs supported on HS-NH2 is mainly attributed to their ultra-small particle size and high surface electron density. Our primary results demonstrate that the organo-modified silica nanospheres are promising solid supports for modifying the electronic properties of metal NPs supported and consequently tailoring their catalytic functions.